Antecedents of Online Purchase Intention Towards Chatbot Services on the Tokopedia E-Commerce Platform - Andrea Filippo Fortuna Purwanto; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to explore the factors that influence online purchase intention on the Tokopedia e-commerce platform, with a particular focus on the role of customer satisfaction as a mediator between chatbot service quality, social entertainment, and social trends. In the increasingly developing digital era, the use of technology such as chatbots is important to improve interactions between customers and sellers. The results of the study indicate that chatbot service quality has a positive and significant effect on customer satisfaction, meaning that the better the quality of service provided, the higher the level of satisfaction felt by customers. In contrast, social entertainment and social trends did not show a significant effect on online purchase intention, indicating that these factors are not strong enough to drive consumer purchasing decisions. This study also confirms that customer satisfaction plays an important role in mediating the relationship between chatbot service quality and online purchase intention, where satisfied customers tend to be more motivated to make repeat purchases. These findings have theoretical and practical implications, encouraging business actors to focus on improving service quality and customer satisfaction to drive purchase intention. However, this study also has limitations, such as the dominance of young respondents and the focus on one e-commerce platform, which limits the generalizability of the results. Therefore, suggestions for future research include analyzing user behavior across multiple e-commerce platforms and implementing a longitudinal approach to gain a more accurate picture of purchasing behavior.